Finite Element Methods: Parallel-Sparse Statics and Eigen-Solutions - Nguyen, Duc Thai (Springer US : Imprint: Springer, 2006)
FEM, and the associated computer software are widely recognized as some of the most effective tools for solutions of large-scale engineering applications. Efficient equation and eigen-solvers play critical roles in solving these problems. Sparse matrix technologies have evolved and are now mature enough that all popular and commercialized FEM codes have inserted sparse solvers into their software. So far, however, few books include detailed discussion and explanation of sparse equation-solvers and Lanczos domain decomposition (DD) or finite element formulation for parallel computing purposes. The material in Finite Element Methods: Parallel-Sparse Statics and Eigen-Solutions has evolved over the past several years from the author's research work and his graduate courses. This book is ideal for graduate students, practicing engineers and researchers, as well as mathematicians and computer scientists. Dr. Duc T. Nguyen is the founding Director of the Institute for Multidisciplinary Parallel-Vector Computation and Professor of Civil and Environmental Engineering at Old Dominion University. Dr. Nguyen has been listed as an ISI Highly Cited Researcher™ in the field of engineering.